NURSING CARE IN MEETING PHYSICAL MOBILITY NEEDS INPATIENTS NON HEMORRHAGIC STROKE IN RSKD DADI MAKASSAR - Nurshiyam, Nurshiyam; Ardi, Muhammad; Basri, Muhammad (Media Keperawatan:Politeknik Kesehatan Makassar, 2020)
Stroke is damage to brain tissue caused by a sudden reduction in or supply of oxygen in the blood. Brain tissue that has decreased oxygen supply will experience decreased function and cell death. The purpose of this study is to provide an overview of nursing care to meet the needs of physical mobility in stroke patients at RSKD Dadi Makassar. The study design was a case study in the form of a nursing care approach in two non-hemorrhagic stroke patients. The results showed both patients experienced weakness of the right limb which caused impaired physical mobility and total self-care deficit. Nursing interventions in patients include ambulation support, mobilization support, range of motion exercises and self-care assistance. Nurses should provide care and education to families about the care of stroke patients who experience physical mobility impairments and self-care deficits. Families also need to provide support to stroke patients undergoing treatment to increase motivation, speed up the recovery process and prevent complications.Â